Wesler, Kit W. 2012 An Archaeology of Religion. - Paul Brazinski (Papers from the Institute of Archaeology, 2013)
Book Review: Wesler, Kit W., An Archaeology of Religion, University Press of America, Inc., New York, 2012.
Keywords: Religion